Determination of the Enantiomerization Barrier of the Residual Enantiomers of C3‐Symmetric Tris[3‐(1‐Methyl‐2‐Alkyl)Indolyl]Phosphane Oxides: Case Study of a Multitasking HPLC Investigation Based on an Immobilized Polysaccharide Stationary Phase. Issue 12 (24th September 2015) - Rizzo, Simona; Menta, Sergio; Benincori, Tiziana; Ferretti, Rosella; Pierini, Marco; Cirilli, Roberto; Sannicolò, Francesco
Abstract: The residual enantiomers of three tris‐(3‐indolyl)‐phosphane oxides bearing different alkyl groups (methyl, ethyl or i ‐propyl) in position 2 of the indole rings constituting the blades were separated on the immobilized type Chiralpak IC column in polar organic and reversed‐phase modes. The goodenantioselectivity and versatility of the IC CSP allowed easy isolation of the enantiomerically highly enriched samples suitable for configurational stability studies. The enantiomerization barriers of residual phosphane oxides were evaluated both by off‐column techniques (CD signal and enantiomeric purity decay kinetics) and by dynamicenantioselective high‐performanceliquid chromatography (HPLC). Chirality 27:888–899, 2015 . © 2015 Wiley Periodicals, Inc. Abstract :